Impact of macroeconomic variables on the Nigerian manufacturing sector - Adedoyin Isola Lawal; Eziekel Oseni; Bukola Bose Lawal-Adedoyin; Joseph IseOlorunkanmi; Abiola J. Asaleye; Henry Inegbedion; M. Santanu; Abigail DickTonye; Opeyemi Eunice Olagunju; Elizabeth Bolatito Ogunwole (Cogent Economics & Finance, 2022)
The essence of this study is to examine the impact of macroeconomic variables and some salient socio-economic and political variables on the manufacturing sub-sector of the Nigerian economy by using the autoregressive distributed lag to analyze data source from 1986 to 2019 within the context of two macroeconomic theories: The Solow growth and the endogenous growth theories. The study noted that both the Solow growth theory and endogenous growth model are valid in the short run for the studied economy, but the result is not the same in the long run, as only the endogenous growth model was valid in the long run. The study noted that to achieve sustainable economic growth powered by strong manufacturing sector, there must be an alignment between the macroeconomic variables employed and the socio-political factors. The findings of the study have some policy implications.
Keywords: B22; C32; E4; E52; 330; Macroeconomic variables; gross domestic product; manufacturing sector; economic growth